2020
DOI: 10.24912/ja.v24i2.693
|View full text |Cite
|
Sign up to set email alerts
|

Fintech Implementation on the Financial Performance of Rural Credit Banks

Abstract: This study aims to determine whether the enactment of BI regulation No.19 / 12 / PBI / 2017 by Financial Services Authority (OJK) in Indonesia has an impact on the performance of banks, especially rural banks (RCB). This’s because RCB are still bound by OJK regulations in lending with a loan mechanism requirements that are quite burdensome customers. The population used in this study is the RCB in Banten Province that registered by OJK for 2014 - 2018, the sampling method used is non probability sampling, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…(Phan et al, 2020) found that the growth of FinTech firms negatively influences bank performance. Also (Suharti & Ardiansyah, 2020) conducted Fintech Implementation on the Financial Performance of Rural Credit Banks. (Baber, H. 2020) assessed the impact of Fintech on customer retention in Islamic banks of Malaysia, The…”
Section: -Literature Reviewmentioning
confidence: 99%
“…(Phan et al, 2020) found that the growth of FinTech firms negatively influences bank performance. Also (Suharti & Ardiansyah, 2020) conducted Fintech Implementation on the Financial Performance of Rural Credit Banks. (Baber, H. 2020) assessed the impact of Fintech on customer retention in Islamic banks of Malaysia, The…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Dengan begitu banyak cara untuk membaca komik, masih cukup banyak dari mereka yang membaca melalui cara ilegal. Komik ilegal bisa dalam bentuk konvensional, yaitu komik yang digandakan tanpa izin atau dalam bentuk modern, yaitu yang disebarluaskan secara digital tanpa izin (Rezy Tri Ardiansyah, 2021). Di zaman yang sudah diselimuti oleh modernisasi, tentunya pembacaan secara digital menjadi pilihan nomor satu.…”
Section: Pendahuluanunclassified